An ergonomic assessment tool for evaluating the effect of back exoskeletons on injury risk. (February 2022) - Zelik, Karl E.; Nurse, Cameron A.; Schall, Mark C.; Sesek, Richard F.; Marino, Matthew C.; Gallagher, Sean
Abstract: Low back disorders (LBDs) are a leading injury in the workplace. Back exoskeletons (exos) are wearable assist devices that complement traditional ergonomic controls and reduce LBD risks by alleviating musculoskeletal overexertion. However, there are currently no ergonomic assessment tools to evaluate risk for workers wearing back exos. Exo-LiFFT, an extension of the Lifting Fatigue Failure Tool, is introduced as a means to unify the etiology of LBDs with the biomechanical function of exos. We present multiple examples demonstrating how Exo-LiFFT can assess or predict the effect of exos on LBD risk without costly, time-consuming electromyography studies. For instance, using simulated and real-world material handling data we show an exo providing a 30 Nm lumbar moment is projected to reduce cumulative back damage by ∼70% and LBD risk by ∼20%. Exo-LiFFT provides a practical, efficient ergonomic assessment tool to assist safety professionals exploring back exos as part of a comprehensive occupational health program. Highlights: Back exos are wearable assist devices that complement ergonomic controls for reducing low back disorder (LBD) risks. However, no ergonomic assessment tools exist to evaluate LBD risks for workers wearing back exos. We introduce Exo-LiFFT, an ergonomic assessment tool adapted from the Lifting Fatigue Failure Tool. Exo-LiFFT is a practical tool that unifies the etiology of LBDs and biomechanical function of exos. Exo-LiFFT can be used to assess or predict the effect of exos on LBD risk without EMG testing.